Tapestry Weavings: Combining Art and Science to Investigate and Illuminate the Lived Experiences of Female High School Principals in Georgia - Hannaford, Barbara Pannell (My University, 2013)
This research project explored the perceptions and experiences of female high school principals. To understand whether a shared essence existed within the phenomena of being a female high school principal in Georgia, a phenomenological focus guided my research. Through in-depth interviews, informal conversations, and electronic communication, this study explored what effective female high school principals do, whether and in what manner their lived experiences shaped their leadership practices, whether commonalities existed as they negotiated their leadership roles at a maledominated level of the profession, and what could be learned from their contextual practices and experiences. Two former and two current female high school principals were interviewed. Interviews were digitally recorded and field notes were taken. Transcripts were coded; emergent themes were identified, and within and cross case analyses were conducted. Findings for each participant were presented in individual portraits, and findings from cross case analysis were presented in a collective portrait. This study presented two distinct but tightly interwoven aspects of female high school principals in Georgia: the personal self and the professional self. Seven common themes emerged in the analysis of participants’ personal selves: (a) personal characteristics; (b) unplanned and circuitous journeys into high school principalships; (c) perceptions of being a high school principal; (d) participants’ definitions of effective leadership; (e) participants’ definitions of effective schools; (f) participants’ perceptions of gender and the high school principalship; and (g) the metaphors participants used. Five common themes emerge in an analysis of participants’ professional selves: (a) modeling expectations and desired behaviors; (b) an emphasis on curriculum and instruction; (c) evidence of the social competence domain of emotional intelligence; (d) students as the heart and soul of participants’ work; and (e) balanced leadership.
A Dissertation by Barbara Pannell Hannaford for Doctor of Education in Curriculum and Instruction at Valdosta State University. December 2011.
Keywords: High school principals; Public Schools; United States -- Georgia; Female Principals; Education; No Child Left Behind; Gender and education